Estratégias bioclimáticas na arquitetura moderna de João Pessoa: Análise aplicada em três residências produzidas entre as décadas 1950 -1980 - Lima, Pollyanna Priscila de Souza (2015)
The modern architecture of the early twentieth century emerges as an international style of the Northern Hemisphere to be reproduced and readapted worldwide. In the tropical Brazilian context, according to the historiography of modern architecture, these buildings were adjusted to regional climatic conditions in virtually all regions of the country between the 1930s and the 1980s. Brazilian northeast was one of the regions where such adjustment was recurrent. However, scholars of environmental comfort are opposed to these historiographical statements. They declare that these buildings were designed with low thermal performance and low bioclimatic quality, both partially due to the absence of technical information about environmental comfort at the time, as a design support for the accomplishment of a more appropriate architecture to the regional climate. Thus, this research aims to highlight strategies and different solutions proposed, regarding the suitability of bioclimatic and efficiency adopted by both modernist architects and precursors of this trend reproduced in the state of Paraiba between the 1950s and the 1980s, emphasizing João Pessoa city, capital of the state of Paraiba. This study is divided into two methodological steps: firstly, there was a qualitative and descriptive analysis based on literature review, definition of bioclimatic criteria for analysis and projectual reading; the next step involved the quantitative analysis of the climate performance of buildings and their surroundings through computer simulations (Autodesk Revit 2015 and Solar Analysis softwares). The relevance of the research is to contribute and to extend studies on Modern Architecture and bioclimatism applied in the Northeast region, specifically in the state of Paraiba, and may also discuss alternative possibilities to contemporary regional architecture.